Proletarian Publics: Leftist and Labour Print in Canada, 1930-1939 - Hasenbank, Andrea Grace (University of Alberta, 2019)
his thesis examines a selection of print materials from the radical and Communist-affiliated Left in the 1930s, a group and time period that are often passed over in assessments of Canadian literature. While similar texts have been studied in the context of legal evidence or political propaganda, they have rarely been considered as print objects in themselves, operating within a network of production, circulation, and response alongside other literary and non-literary media. In looking at the 1930s, a moment when the project of Canada was acutely challenged by the political and economic forces of the Great Depression, I see an equal challenge to scholars and critics by writers and readers struggling to organize from below. By considering examples of Canadian proletarian print from different points along the communication cycle, this project seeks to connect the imaginary aspirations and rhetorical strategies of these texts to the material contexts of their producers and readers. Chapter One addresses the existing gap in Canadian literary history, which maintains a liberal orientation throughout its associated institutions, approaches and subjects; this orientation has been upheld through political and legal structures hostile to proletarian movements. This chapter discusses Ronald Liversedge’s Recollections of the On-to-Ottawa Trek as a text that highlights and crosses such institutional boundaries. Chapter Two takes up the methods of book history, using the example of the “Worker’s Pamphlet Series” to discuss expanding this approach to include material such as pamphlets, periodicals, and manifestos as part of an explicit class analysis. Chapter Three analyzes the self-reflexive circulation of proletarian print in the restrictive legal environment created by Section 98 of the Criminal Code through materials produced by the Canadian Labour Defense League. Chapter Four examines surveillant readings and misreadings as they intercept proletarian print, using the Edmonton Hunger March and the subsequent pamphlet “The Alberta Hunger-March.” By mapping locations associated with this event and with the print economy in 1932 Edmonton, Chapter Five considers the formation of proletarian publics as highly localized interpretive communities, and how the application of tools such as GIS mapping might further re-center readers’ material lives in the analysis of print culture. As a whole, this dissertation demonstrates how the methods of analysis and historicization offered by book history can and should be applied to bring proletarian print and readers into conversation with the wider patterns of Canadian writing through the twentieth century. This is a necessary confrontation: as the study of Canadian literature begins to acknowledge the construction and contestation of our national myths, it must also avow the lasting political consequences for those who have been excluded.